Comparison of CFD-DEM and TFM simulations of single bubble injection in 3D gas-fluidized beds with MRI results. (2nd November 2021) - Xi, K.; Guo, Q.; Boyce, C.M.
Highlights: CFD-DEM and TFM fluidization simulations compared with single bubble MRI results. Simulations predict taller and narrower bubbles than seen experimentally. Neither CFD-DEM or TFM predicts bubble and particle behavior more accurately. Abstract: Predictions for bubble and particle dynamics surrounding a single bubble injected into an incipiently cylindrical fluidized bed from CFD-DEM and TFM simulations using different drag laws were compared with prior MRI results. This comparison allows for quantitative assessment of the accuracy of simulations for deterministic behavior of a single bubble as compared to statistical comparisons of chaotic free bubbling behavior as conducted in several prior studies. The comparison shows that simulations capture bubble rise velocity and particle velocity data surrounding bubbles fairly well. However, simulations tend to predict bubble shapes which are taller and narrower with larger wake angles than those observed experimentally. Changing drag laws does not have a significant effect on results, and significant quantitative differences are observed in moving from CFD-DEM to TFM simulations, yet neither provides predictions which are definitively better across a wide range of metrics. Some recommendations, including the use of novel drag laws and frictional solids stress models in TFM as well as the consideration of particle size distribution that may improve the prediction performance, are provided.